2017
DOI: 10.1016/j.ijrobp.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Carbon-Ion Radiation Therapy for Mucosal Melanoma of the Head and Neck: Subanalysis of the Japan Carbon-Ion Radiation Oncology Study Group (J-CROS) Study (1402 HN)

Abstract: Carbon-ion RT is a promising treatment option for MMHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 25 publications
(24 reference statements)
6
78
1
Order By: Relevance
“…The present study included 19 patients (66%) who received concurrent chemotherapy, including DTIC, which did not significantly improve prognosis based on 5‐year rates of 87.4% for local control and 48.8% for OS. Nevertheless, a retrospective multicenter study of C‐ion RT for head and neck mucosal melanoma revealed that a survival benefit was associated with concurrent chemotherapy, including DTIC . Moreover, complementary activity against melanoma has recently been reported for ipilimumab (a cytotoxic T‐lymphocyte‐associated antigen‐4 checkpoint inhibitor) and nivolumab (a programmed death‐1 checkpoint inhibitor), and Karlsson et al have reported that checkpoint inhibitors are more effective than immunotherapy or chemotherapy in terms of survival and tumor response among patients with stage III/IV unresectable cutaneous melanoma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study included 19 patients (66%) who received concurrent chemotherapy, including DTIC, which did not significantly improve prognosis based on 5‐year rates of 87.4% for local control and 48.8% for OS. Nevertheless, a retrospective multicenter study of C‐ion RT for head and neck mucosal melanoma revealed that a survival benefit was associated with concurrent chemotherapy, including DTIC . Moreover, complementary activity against melanoma has recently been reported for ipilimumab (a cytotoxic T‐lymphocyte‐associated antigen‐4 checkpoint inhibitor) and nivolumab (a programmed death‐1 checkpoint inhibitor), and Karlsson et al have reported that checkpoint inhibitors are more effective than immunotherapy or chemotherapy in terms of survival and tumor response among patients with stage III/IV unresectable cutaneous melanoma .…”
Section: Discussionmentioning
confidence: 99%
“…Carbon ion RT (C‐ion RT) has a higher linear energy transfer and a greater relative biological effectiveness (RBE) than photon RT . Furthermore, various reports have described promising results from C‐ion RT for radioresistant tumors, such as salivary gland carcinoma (SGC) and mucosal melanoma of the head and neck . Koto et al evaluated 46 patients with locally advanced parotid gland carcinoma who were followed‐up for a median of 62 months and reported 5‐year rates of 74.5% for local control and 70.1% for overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, adjuvant postoperative radiation therapy may improve locoregional control but does not appear to affect survival . Although mucosal melanomas are known to be radioresistant, a recent retrospective multicenter study showed that carbon ion radiation therapy resulted in good local control and overall survival with acceptable toxicities . Complete surgical excision with clear margins is one of the most important prognostic factors .…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from head and neck malignancies and treated with C‐ion RT between November 2003 and December 2014 were included. Detailed inclusion criteria have been described previously . Patients with previous irradiation to the head and neck were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective multicenter study to evaluate the clinical outcomes of C‐ion RT for head and neck malignancies was performed (Japan Carbon‐Ion Radiation Oncology Study Group [J‐CROS] Study: 1402 HN). The clinical outcomes of the respective major histological types of head and neck malignancies have already been reported . The 5‐year local control and overall survival (OS) rates among patients with adenoid cystic carcinoma, mucosal melanoma, and adenocarcinoma of 68% and 74%, 72.3% and 44.6%, and 79.3% and 60.4%, respectively, were also reported …”
Section: Introductionmentioning
confidence: 98%